2003
DOI: 10.5483/bmbrep.2003.36.5.499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diazinon, an Organophosphate Insecticide, on Plasma Lipid Constituents in Experimental Animals

Abstract: There has been increasing interest in studying the various effects of organophosphate insecticides in humans and experimental animals. Only a few data are available on the effect of the organophosphate insecticide, diazinon, on lipid metabolism. The aim of this study was to evaluate the effect of diazinon on plasma lipid constituents in mammalian animals. The plasma levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 25 publications
9
26
0
Order By: Relevance
“…These may be attributed to the increased fat catabolism in response to LCT. 50 Our results also showed a significant increase of serum bilirubin level in LCT intoxicated rats. The increased level of total bilirubin in treated female rats is an indicator of hyper-bilirubinemia, a useful indicator of hepatocellular dysfunction.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These may be attributed to the increased fat catabolism in response to LCT. 50 Our results also showed a significant increase of serum bilirubin level in LCT intoxicated rats. The increased level of total bilirubin in treated female rats is an indicator of hyper-bilirubinemia, a useful indicator of hepatocellular dysfunction.…”
Section: Discussionsupporting
confidence: 69%
“…(1/11 th LD 50 ) in female rat (Figure 1). No differences in food and water consumption were seen in last consecutive four days of treatment in the experimental schedule but there was little non-significant alterations observed in food consumption at the exposure dose levels of 1/4 th and 1/3 rd LD 50 .…”
Section: Changes In Body Weight Food and Water Intakementioning
confidence: 96%
“…Similarly, low-HDL-c has also been reported in rats dosed repeatedly with diazinon (Ibrahim and El-Gamal, 2003). HDL, which is mainly synthesized in the liver and intestinal cells plays an important role in cholesterol efflux from tissues and carries it back to the liver for removal as bile acids (Shakoori et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have partly implicated oxidative stress in the molecular mechanism of CPFinduced hepatotoxicity (Goel et al, 2005;Ambali et al, 2007;. A number of studies have shown alterations in lipid profiles following OP exposure (McGill et al, 1981;Quistad et al, 2001;Ibrahim and El-Gamal, 2003;El-Banna et al, 2009;El-Mazoudy et al, 2011). However, studies involving the mitigation of OP induced alterations of lipid profiles by readily available and cheap antioxidant molecules such as vitamin C become essential in the light of the current environmental and health challenges posed by OP insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphates, including DDVP have already been reported to elevate plasma triglyceride [27,28]. The elevated plasma triglyceride concentration may be attributed to DDVP induced inhibition of lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%